IMPLEMENTATION OF DIGITAL MEDIA IN LEARNING ISLAMIC RELIGIOUS EDUCATION IN THE ERA OF INDUSTRIAL REVOLUTION 4.0 - Damayanti, Ervinna; Mundir, Mundir; Sutomo, Moh.; Tamami, Badrut (Islamic Management: Jurnal Manajemen Pendidikan Islam, 2025)
The era of Industrial Revolution 4.0 brings significant changes in various fields, including education. Digital media has become an important instrument to support more interactive and effective learning, including in Islamic Religious Education (PAI). This article aims to explore the implementation of digital media in Islamic Education learning, its benefits, challenges faced, and strategic solutions to overcome these obstacles. The results show that digital media contributes to increasing students' interest in learning, interaction, and understanding of PAI materials. However, obstacles such as limited teacher competence in technology, uneven internet access, and students' economic disparity are still the main challenges. Digital literacy training for teachers, procurement of technology infrastructure, and provision of relevant digital-based content are the keys to optimizing PAI learning.